The Effect of Memory Reading Strategy Implemented by Second Year Student UNISMA on Their Achievement - Durro Tussaminah; mutmainnah mustafa; imam wahyudi karimullah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
Abstract: This study aimed at investigating the different interaction effect between high and low student memory reading strategy on their reading achievement. The respondents of this study were fourth semester students of English department UNISMA. The total of this sample is 42 students. In collecting the data, the researcher needed to know the level of students’ memory reading skill and their reading achievement. So the researcher decided to use questioner and collect the reading midterm test score from their reading lecture. The researcher used quantitative independent t-test research design with variables students’ memory reading strategies and their reading achievement. The questioner was adapted from Oxford (1990) which is this questioner also used by many previous researchers that already test the validity and reliability of this questioner. The result of this study showed the different mean score between high and low level of memory reading strategy. 66.14 for high level of memory reading strategy and 71.05 for low level of memory reading strategy. The result analyze of the mean difference between high and low student memory reading strategy of this study = -4.914 > 0.05. The mean different -4.914 it got from 66.14-71.05 so the result was -4.914. Then, the sig (2- tailed) = 0.241> 0.05 so from the result, the researcher can conclude that there is no significantly different effect between high and low students memory reading strategy on their achievement at English department of UNISMA.